Same-Sex Couples and the Marital Surplus: The Importance of the Legal Environment - Scott M. Delhommer; Daniel S. Hamermesh (Institute of Labor Economics (IZA), 2020)
Same-sex couples' marital surplus, their excess total income over that predicted by their work times and predicted wages, increases little as the duration of their relationship lengthens. When/where same-sex marriage is legal, it rises sharply as duration increases. The availability of legal domestic partnership or civil union has no effect on the surplus. The likelihood of home ownership conditional on demographic characteristics also increases with partnerships' duration only when/where same-sex marriage is legal. These results, based on data from the American Community Survey 2013-17, support the notion that greater legal protection enhances partners' incentives to invest in their relationship.
Keywords: J12; J16; K30; 330; gains from marriage; same-sex partnership; home ownership